Strife and Peace - Bremer, Fredrika, 1801-1865; Howitt, Mary (Mary Botham), 1799-1888 (Salt Lake City, UT : Project Gutenberg, 2006)
"Strife and Peace" by Fredrika Bremer is a novel written in the mid-19th century. The book explores themes of nature, personal struggles, and the complex relationships between its characters in Norway, particularly focusing on the lives of a widow named Mrs. Astrid and her two caretakers, Susanna and Harald. Through their interactions and the beautiful but harsh Norwegian landscape, the story delves into the emotional and societal conflicts faced by individuals. The opening of "Strife and Peace" vividly describes the majestic Norwegian countryside, invoking a sense of timelessness and deep connection to nature. As the narrative unfolds, readers are introduced to Mrs. Astrid, an elderly and melancholic widow who has returned to her childhood home, as well as Susanna Björk, a spirited young woman seeking purpose in her life. The strong dynamic between Susanna and Harald, the estate steward, is characterized by playful disputes about their respective countries, Norway and Sweden, bringing levity to their lives amidst Mrs. Astrid's sorrow. This initial section establishes the deep emotional struggles of the characters and sets the stage for exploring themes of resilience, identity, and the human condition against the backdrop of the serene yet tumultuous Norwegian landscape. (This is an automatically generated summary.)
Release date is 2006-12-21
E-text prepared by Barbara Tozier, Bill Tozier, Janet Blenkinship, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Norway -- Social life and customs -- 19th century -- Fiction